Penerapan Teknologi Nano Ekstrak Meniran pada Pakan dan Pengenalan Teknologi Silase untuk Meningkatkan Kemandirian Ekonomi Kelompok Ternak Sapi Perah di Desa Sendang, Kabupaten Tulungagung, Jawa Timur: Application of Nano Technology of Phyllanthus niruri Extract in Feed and Introduction of Silage Technology to Improve the Economic Independence of Dairy Cattle Farmer Groups in Sendang Village, Tulungagung Regency, East Java - Hidanah, Sri; Sabdoningrum, Emy Koestanti; Lokapirnasari, Widya Paramita; Bayuny, Ahmad Fadlur Rahman (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The productivity of dairy cows in Sendang Village, Tulungagung Regency, remains below optimal potential, averaging only 4–10 liters per head per day, due to limited access to quality feed and suboptimal livestock health management. This community service program aims to enhance productivity through two feed innovations: nanotechnology-based Phyllanthus niruri extract to improve livestock health and metabolic efficiency, and silage feed to ensure the year-round availability of nutritious feed. The methods employed include socialization, technical training, and distribution of both products to 20 dairy farmers who are members of KPUD Tani Wilis. The application of these two technologies has the potential to increase both the quantity and quality of milk production, while also supporting the achievement of the Sustainable Development Goals (No Poverty, Zero Hunger, Decent Work and Economic Growth, Responsible Consumption and Production, and Climate Action).